Effect of the Sequential Inoculation of Non-Saccharomyces/Saccharomyces on the Anthocyans and Stilbenes Composition of Tempranillo Wines - Escribano-Viana, Rocío; Portu, Javier; Garijo, Patrocinio; López, Rosa; Santamaría, Pilar; López-Alfaro, Isabel; Gutiérrez, Ana Rosa; González-Arenzana, Lucía (Frontiers in Microbiology, 2019)
The phenolic compounds of red wines are responsible for their colour, astringency, and antioxidant properties. The fermentative yeasts might be used to modulate wines in terms of their colour, aroma and probably healthy properties. In this study, six non-Saccharomyces species were tested because they might enhance the properties of red Tempranillo wines from Rioja. The results confirmed that the anthocyanins and stilbenes composition of wine can be modulated with the use of a specific fermentation starter. M. pulcherrima, Z. bailii, C. zeylanoides, and T. delbrueckii achieved the greatest improvements of the monomeric anthocyanin composition, and the latter three yeast species achieved the best results of stilbene composition when compared to S. cerevisiae and the other non-Saccharomyces yeasts. Overall, results suggested that the use of M. pulcherrima, Z. bailii, C. zeylanoides and T. delbrueckii as fermentation starters could be of great interest to achieve wines with better colour and likely healthy properties.